Wear-resistant and heat-insulating rigid foam material and preparation method thereof

Through the deep common crystal solvent treatment of cellulose and combined with polyvinyl alcohol and ZIF-8/PDA, Ice template and directional frozen device are used to build a steel-type muddy structure, which solves the difficulty of achieving excellent mechanical performance and blocking at the same time. The problem of burning, low thermality, and lightweight environmental protection characteristics have realized high -performance, environmentally friendly hard foam materials.

CN119350697APending Publication Date: 2025-01-24SHAANXI UNIV OF SCI & TECH
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411450672.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

It is difficult for existing environmentally friendly cellulose-based foam materials to achieve excellent mechanical properties, flame retardancy, low thermal conductivity and lightweight environmental protection characteristics simultaneously.

Method used

Through deep-crystal solvents to treat cellulose to generate nanoland fibers, combined with biodegradable polyvinyl alcohol and ZIF-8 and PDA synthesized in situ, frozen drying and drying of ice templates and directional frozen devices are used to build steel-type dirt structure.

Benefits of technology

A hard foam material with excellent mechanical strength, extremely low thermal conductivity and good thermal insulation performance, and the material itself is light and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350697A_ABST
    Figure CN119350697A_ABST
Patent Text Reader

Abstract

The invention discloses a wear-resistant and heat-insulating hard foam material and a preparation method thereof. The preparation method comprises the following steps: treating cellulose through a deep eutectic solvent to convert the cellulose into nano fibril; freeze-drying by adopting an ice template method to obtain a nanocellulose aggregate with a layered structure; then, growing ZIF-8 nanocrystals on the surface of the nanocellulose aggregate, and obtaining CNF-A (at) ZIF-8; separating the CNF-A-coated ZIF-8 from the liquid phase through filtering and washing treatment, and coating the surface of the CNF-A-coated ZIF-8 with polydopamine in a Tris buffer solution so as to obtain CNF-A-coated ZIF-8 / PDA; further dispersing CNF-A ZIF-8 / PDA in water to obtain dispersion slurry, adding a polyvinyl alcohol aqueous solution and epichlorohydrin into the slurry, and stirring and mixing to obtain a CZPP precursor; performing freezing treatment on the CZPP precursor; and finally, carrying out freeze drying treatment to obtain the CZPP rigid foam. The CZPP prepared by the invention has the characteristics of excellent mechanical strength, good heat insulation performance, wear resistance and light weight, and the main body raw materials CNF and PVA are degradable materials, so that the CZPP has the characteristic of environmental protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional materials, relates to foam materials, and specifically relates to a method for preparing a wear-resistant and heat-insulating hard foam material. Background Art

[0002] Thermal insulation materials are divided into three categories: porous materials, heat-reflective materials and vacuum materials. The former uses the pores contained in the material itself to insulate heat, because the thermal conductivity of air or inert gas in the gap is very low, such as foam materials, fiber materials, etc.; heat-reflective materials have a high reflection coefficient and can reflect heat, such as gold, silver, nickel, aluminum foil or metal-plated polyester, polyimide film, etc. Vacuum insulation materials use the internal vacuum of the material to block convection to insulate heat.

[0003] More than 40% of the world's energy is used for thermal management of buildings to keep indoor temperatures moderate. In order to advocate energy conservation and consumption reduction, petroleum-based insulation materials such as polyurethane and polystyrene foams are widely used in commerce. However, petroleum-based materials are harmful to the environment and human health, which has become an important issue worldwide. Cellulose insulation foam materials have attracted widespread attention in the field of materials science and engineering in recent years due to their excellent environmental friendliness and good thermal insulation properties. As a natural polymer material, cellulose has good biodegradability and renewability. Compared with traditional synthetic foam materials such as polystyrene (EPS) or polyurethane (PU), cellulose foam has significantly reduced environmental impact during post-use disposal. These materials use cellulose as the main component and form a porous structure through foaming, thus having excellent thermal insulation properties and low density. Research in recent years has been devoted to further improving the thermal insulation effect of these foam materials. Researchers have achieved this goal by optimizing the pore structure of the foam and modifying cellulose. For example, nanocellulose or cellulose nanocrystals are used to enhance the structural stability and thermal insulation of the foam. Studies have found that the thermal insulation properties of the material can be significantly improved by controlling the pore size and distribution of the foam. In addition, the application of modified cellulose, such as the introduction of hydrophobic groups, can also improve the moisture resistance of foam materials, thereby maintaining good thermal insulation performance in high humidity environments. However, the manufacture of environmentally friendly cellulose-based foam materials with excellent mechanical properties, flame retardancy and low thermal conductivity remains a great challenge. Summary of the invention

[0004] In view of the deficiencies in the prior art, the object of the present invention is to provide a wear-resistant and heat-insulating rigid foam material and a preparation method thereof, wherein the material has excellent mechanical strength, extremely low thermal conductivity, and is lightweight and environmentally friendly.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A method for preparing a wear-resistant and heat-insulating rigid foam material comprises the following steps:

[0007] Step 1, treating cellulose with a deep eutectic solvent consisting of choline chloride and oxalic acid dihydrate to convert it into nanofibril CNF, and filtering and washing the CNF to remove excess solvent;

[0008] Wherein, by weight, the amount of choline chloride is 40-45 parts, the amount of oxalic acid dihydrate is 30-35 parts, and the amount of cellulose is 8-10 parts;

[0009] Step 2, dispersing the CNF prepared in step 1 in distilled water and freezing it, and then freeze-drying it to obtain nanocellulose aggregates CNF-A with a layered structure;

[0010] Wherein, in parts by weight, the amount of CNF is 5 to 10 parts, and the amount of distilled water is 200 to 300 parts;

[0011] Step 3, dispersing the CNF-A prepared in step 2 in methanol and adding zinc nitrate hexahydrate and dimethylimidazole, stirring continuously for 18 to 24 hours, filtering and washing to obtain CNF-A@ZIF-8;

[0012] Wherein, in parts by weight, the amount of CNF-A is 5 to 10 parts, the amount of methanol is 500 to 800 parts, the amount of zinc nitrate hexahydrate is 6 to 10 parts, and the amount of dimethylimidazole is 16 to 21 parts;

[0013] Step 4, dispersing the CNF-A@ZIF-8 and dopamine hydrochloride prepared in step 3 in a Tris buffer and stirring the dispersion at room temperature for 20 to 24 hours to obtain CNF-A@ZIF-8 / PDA, and obtaining a CNF-A@ZIF-8 / PDA solid by freeze drying;

[0014] Wherein, by weight, the amount of CNF-A@ZIF-8 is 5 to 8 parts, the amount of dopamine hydrochloride is 17 to 24 parts, and the amount of Tris buffer is 800 to 1200 parts;

[0015] Step 5, dispersing the CNF-A@ZIF-8 / PDA prepared in step 4 in distilled water to obtain a dispersion slurry, and adding 10 wt % polyvinyl alcohol aqueous solution and epichlorohydrin to the slurry for stirring and mixing to obtain a CNF-A@ZIF-8 / PDA / PVA precursor, namely a CZPP precursor;

[0016] Among them, in parts by weight, the amount of CNF-A@ZIF-8 / PDA is 5 to 10 parts, the amount of distilled water is 100 to 150 parts, the amount of polyvinyl alcohol aqueous solution is 150 to 200 parts, and the amount of epichlorohydrin is 15 to 20 parts;

[0017] Step six, placing the CZPP precursor prepared in step five in a mold for freezing treatment, and then freeze-drying to obtain CZPP rigid foam.

[0018] The present invention also has the following technical features:

[0019] Preferably, the method for treating cellulose with a deep eutectic solvent in step 1 is to mix the raw materials and then heat and stir them at 100 to 120° C. for 3 to 6 hours.

[0020] Preferably, the washing method described in step 1 is washing with distilled water 3 to 5 times.

[0021] Preferably, the freezing treatment in step 2 and step 6 is performed at -18 to -20°C for 12 to 16 hours;

[0022] The freeze-drying process described in step 2, step 4 and step 6 is freeze-drying at -56 to -64°C for 48 to 50 hours.

[0023] Preferably, the washing method in step three is to wash once with methanol and then wash 3 to 5 times with ethanol.

[0024] Preferably, the preparation method of the Tris buffer described in step 4 comprises: adding 3.0285 g Tris to 500 mL distilled water, and then adding 0.6125 mL concentrated hydrochloric acid and shaking well; the pH of the Tris buffer is 8.5.

[0025] Preferably, the stirring in step 5 is carried out by using a magnetic stirrer for 30 to 40 minutes.

[0026] The present invention also protects a wear-resistant and heat-insulating rigid foam material prepared by the method as described above.

[0027] Compared with the prior art, the present invention has the following technical effects:

[0028] The present invention firstly transforms cellulose into nanofibrils by treating cellulose with a deep eutectic solvent, uses cellulose as the main frame, uses biodegradable polyvinyl alcohol as the polymer matrix, and adopts an ice template method to freeze-dry the cellulose nanofibrils to obtain nanocellulose aggregates with a layered structure. In situ synthesized ZIF-8 and PDA are used as functional materials, and a specific directional freezing device is used to achieve a perfect combination of the components, thereby obtaining a CZPP hard foam with excellent mechanical strength, good thermal insulation performance, wear resistance and light weight.

[0029] The main raw materials CNF and PVA of the present invention are both degradable materials and have environmental protection characteristics;

[0030] The technology of the present invention explores the optimal ratio between nanocellulose and ZIF-8 raw materials, and achieves high-density loading of inorganic nanoparticles on the surface of layered cellulose aggregates; the improved directional freezing device constructs a reinforced concrete structure inside the CZPP rigid foam, so that it can obtain excellent mechanical strength while retaining a high porosity; CZPP rigid foam has an extremely low thermal conductivity (0.048W / mK), which is comparable to commercial insulation building materials (0.05W / mK), and exhibits excellent thermal insulation properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 is a schematic diagram of a directional freezing device used in the present invention;

[0032] Figure 2 is a SEM image of the nanocellulose aggregates prepared in Example 1;

[0033] Figure 3 is a SEM image of CNF-A@ZIF-8 / PDA prepared in Example 1;

[0034] Figure 4 is a SEM image of the internal structure of the CZPP rigid foam prepared in Example 1;

[0035] Figure 5 is a mapping diagram of the internal structural elements of the CZPP rigid foam prepared in Example 1;

[0036] Figure 6 is a macroscopic photograph of the CZPP rigid foam prepared in Example 1;

[0037] Figure 7 is an infrared thermal image of the CZPP rigid foam prepared in Example 2 on a hot plate;

[0038] Figure 8 is a temperature variation diagram of the CZPP rigid foam prepared in Example 2 on a hot plate;

[0039] Fig. 9 is an infrared thermal image of the CZPP rigid foam prepared in Example 3 on a cold plate;

[0040] Fig.10 is a temperature variation diagram of the CZPP rigid foam prepared in Example 3 on a cold plate;

[0041] Fig.11 is the thermal conductivity of the CZPP rigid foam and other thermal insulation materials prepared in Example 4;

[0042] Fig.12 is a curve diagram of the surface friction coefficient of the CZPP rigid foam prepared in Example 1;

[0043] Fig.13 This is the surface wear morphology of the CZPP rigid foam prepared in Example 1. DETAILED DESCRIPTION

[0044] The specific contents of the present invention are further explained in detail below in conjunction with embodiments.

[0045] In the following examples, the deep eutectic solvent composed of choline chloride and oxalic acid dihydrate was obtained by heating and melting a solid mixture of the two at 80°C;

[0046] During the stirring process, the rotor speed of the magnetic stirrer is 1000-1200 rpm;

[0047] The preparation method of Tris buffer comprises: adding 3.0285 g of Tris into 500 mL of distilled water, and then adding 0.6125 mL of concentrated hydrochloric acid and shaking well; the pH of the Tris buffer is 8.5.

[0048] Example 1

[0049] A method for preparing a wear-resistant and heat-insulating rigid foam material comprises the following steps:

[0050] Step 1, 8.0 g of cellulose was added to a deep eutectic solvent consisting of 40.0 g of choline chloride and 30.0 g of oxalic acid dihydrate and heated and stirred at 100° C. for 3 hours, and then washed with distilled water for 3 times to obtain CNF;

[0051] Step 2: 5.0 g CNF was dispersed in 200 g distilled water and frozen at -18 °C for 12 hours, and then the frozen CNF was freeze-dried at -56 °C for 48 hours to obtain CNF aggregates CNF-A with a layered structure;

[0052] Step 3: Disperse 5.0 g CNF-A in 500 g methanol and add 6.0 g zinc nitrate hexahydrate and 16.0 g dimethylimidazole. After continuous stirring for 18 hours, wash the mixture once with methanol and then three times with ethanol to obtain CNF-A@ZIF-8.

[0053] Step 4: Disperse 5.0 g CNF-A@ZIF-8 and 17.0 g dopamine hydrochloride in 800 g Tris buffer and stir the dispersion at room temperature for 20 hours to obtain CNF-A@ZIF-8 / PDA, and obtain CNF-A@ZIF-8 / PDA solid by the same freeze-drying process as step 2;

[0054] Step 5: Disperse 5.0 g of CNF-A@ZIF-8 / PDA in 100 g of distilled water to obtain a dispersion slurry, and add 150 g of a 10 wt% polyvinyl alcohol aqueous solution and 15.0 g of epichlorohydrin to the slurry for stirring and mixing (1000 rpm / 30 min) to obtain a CZPP precursor;

[0055] Step 6: Place the CZPP precursor in a specific mold and place it in a specific directional freezing device ( Figure 1 ) and then the CZPP rigid foam is obtained by the same freeze-drying process as step 2.

[0056] Example 2

[0057] A method for preparing a wear-resistant and heat-insulating rigid foam material comprises the following steps:

[0058] Step 1, 10.0 g of cellulose was added to a deep eutectic solvent consisting of 45.0 g of choline chloride and 35.0 g of oxalic acid dihydrate and heated and stirred at 120° C. for 6 hours, and then washed with distilled water for 5 times to obtain CNF;

[0059] Step 2: 10.0 g CNF was dispersed in 300 g distilled water and frozen at -20 °C for 16 hours, and then the frozen CNF was freeze-dried at -64 °C for 50 hours to obtain CNF aggregates CNF-A with a layered structure;

[0060] Step 3: Disperse 10.0 g CNF-A in 800 g methanol and add 10.0 g zinc nitrate hexahydrate and 21.0 g dimethylimidazole. After continuous stirring for 24 hours, wash the mixture once with methanol and then wash it 5 times with ethanol to obtain CNF-A@ZIF-8.

[0061] Step 4: Disperse 8.0 g CNF-A@ZIF-8 and 24.0 g dopamine hydrochloride in 1200 g Tris buffer and stir the dispersion at room temperature for 24 hours to obtain CNF-A@ZIF-8 / PDA, and obtain CNF-A@ZIF-8 / PDA solid by the same freeze-drying process as step 2;

[0062] Step 5: Disperse 10.0 g of CNF-A@ZIF-8 / PDA in 150 g of distilled water to obtain a dispersion slurry, and add 200 g of a 10 wt% polyvinyl alcohol aqueous solution and 20.0 g of epichlorohydrin to the slurry and stir and mix (1200 rpm / 40 min) to obtain a CZPP precursor;

[0063] Step 6: Place the CZPP precursor in a specific mold and place it in a specific directional freezing device ( Figure 1) and then the CZPP rigid foam is obtained by the same freeze-drying process as step 2.

[0064] Example 3

[0065] A method for preparing a wear-resistant and heat-insulating rigid foam material comprises the following steps:

[0066] Step 1, 9.0 g of cellulose was added to a deep eutectic solvent consisting of 42.0 g of choline chloride and 33.0 g of oxalic acid dihydrate and heated and stirred at 110° C. for 4 hours, and then washed with distilled water for 4 times to obtain CNF;

[0067] Step 2: 8.0 g CNF was dispersed in 250 g distilled water and frozen at -20 °C for 14 hours, and then the frozen CNF was freeze-dried at -58 °C for 48 hours to obtain CNF aggregates CNF-A with a layered structure;

[0068] Step 3, 8.0 g CNF-A was dispersed in 700 g methanol and 8.0 g zinc nitrate hexahydrate and 18.0 g dimethylimidazole were added. After continuous stirring for 20 hours, the mixture was washed once with methanol and then washed 5 times with ethanol to obtain CNF-A@ZIF-8;

[0069] Step 4: Disperse 6.0 g CNF-A@ZIF-8 and 20.0 g dopamine hydrochloride in 1000 g Tris buffer and stir the dispersion at room temperature for 20 hours to obtain CNF-A@ZIF-8 / PDA, and obtain CNF-A@ZIF-8 / PDA solid by the same freeze-drying process as step 2;

[0070] Step 5: Disperse 8.0 g of CNF-A@ZIF-8 / PDA in 120 g of distilled water to obtain a dispersion slurry, and add 180 g of a 10 wt% polyvinyl alcohol aqueous solution and 16.0 g of epichlorohydrin to the slurry for stirring and mixing (1000 rpm / 35 min) to obtain a CZPP precursor;

[0071] Step 6: Place the CZPP precursor in a specific mold and place it in a specific directional freezing device ( Figure 1 ) and then the CZPP rigid foam is obtained by the same freeze-drying process as step 2.

[0072] Example 4

[0073] A method for preparing a wear-resistant and heat-insulating rigid foam material comprises the following steps:

[0074] Step 1: 10.0 g of cellulose was added into a deep eutectic solvent consisting of 40.0 g of choline chloride and 35.0 g of oxalic acid dihydrate and heated and stirred at 120° C. for 4 hours, and then washed with distilled water for 4 times to obtain CNF;

[0075] Step 2: 8.0 g CNF was dispersed in 300 g distilled water and frozen at -18°C for 14 hours, and then the frozen CNF was freeze-dried at -64°C for 48 hours to obtain CNF aggregates CNF-A with a layered structure;

[0076] Step 3: Disperse 6.0 g CNF-A in 700 g methanol, add 7.0 g zinc nitrate hexahydrate and 19.0 g dimethylimidazole, and after continuous stirring for 20 hours, wash the mixture once with methanol and then wash it four times with ethanol to obtain CNF-A@ZIF-8;

[0077] Step 4: Disperse 6.0 g CNF-A@ZIF-8 and 20.0 g dopamine hydrochloride in 900 g Tris buffer and stir the dispersion at room temperature for 24 hours to obtain CNF-A@ZIF-8 / PDA, and obtain CNF-A@ZIF-8 / PDA solid by the same freeze-drying process as step 2;

[0078] Step 5: Disperse 6.0 g of CNF-A@ZIF-8 / PDA in 150 g of distilled water to obtain a dispersion slurry, and add 200 g of a 10 wt% polyvinyl alcohol aqueous solution and 18.0 g of epichlorohydrin to the slurry and stir and mix (1200 rpm / 40 min) to obtain a CZPP precursor;

[0079] Step 6: Place the CZPP precursor in a specific mold and place it in a specific directional freezing device ( Figure 1 ) and then the CZPP rigid foam is obtained by the same freeze-drying process as step 2.

[0080] Example 5

[0081] A method for preparing a wear-resistant and heat-insulating rigid foam material comprises the following steps:

[0082] Step 1: 10.0 g of cellulose was added into a deep eutectic solvent consisting of 40.0 g of choline chloride and 35.0 g of oxalic acid dihydrate and heated and stirred at 120° C. for 4 hours, and then washed with distilled water for 4 times to obtain CNF;

[0083] Step 2: 5.0 g CNF was dispersed in 200 g distilled water and frozen at -19°C for 14 hours, and then the frozen CNF was freeze-dried at -64°C for 49 hours to obtain CNF aggregates CNF-A with a layered structure;

[0084] Step 3: Disperse 6.0 g CNF-A in 700 g methanol, add 7.0 g zinc nitrate hexahydrate and 19.0 g dimethylimidazole, and after continuous stirring for 20 hours, wash the mixture once with methanol and then wash it four times with ethanol to obtain CNF-A@ZIF-8;

[0085] Step 4: Disperse 6.0 g CNF-A@ZIF-8 and 20.0 g dopamine hydrochloride in 900 g Tris buffer and stir the dispersion at room temperature for 22 hours to obtain CNF-A@ZIF-8 / PDA, and obtain CNF-A@ZIF-8 / PDA solid by the same freeze-drying process as step 2;

[0086] Step 5: Disperse 6.0 g of CNF-A@ZIF-8 / PDA in 150 g of distilled water to obtain a dispersion slurry, and add 200 g of a 10 wt% polyvinyl alcohol aqueous solution and 18.0 g of epichlorohydrin to the slurry and stir and mix (1200 rpm / 40 min) to obtain a CZPP precursor;

[0087] Step 6: Place the CZPP precursor in a specific mold and place it in a specific directional freezing device ( Figure 1 ) and then the CZPP rigid foam is obtained by the same freeze-drying process as step 2.

[0088] Figure 1 Schematic diagram of the directional freezing device used in Examples 1 to 5. A liquid nitrogen thermos is placed inside the incubator, with a pure copper lid on top. There is a hollow copper tube at the bottom of the lid, and a sealing material is wrapped around it. The liquid nitrogen slowly evaporates at the bottom of the thermos and lowers the temperature of the copper lid, causing the CZPP in the top mold to be frozen and forming a reinforced concrete structure inside it.

[0089] Figure 2 is a SEM image of the nanocellulose aggregates prepared in Example 1. Figure 2It can be seen that CNF forms aggregated and large-sized layered structures during the freeze-drying process. Nanocellulose particles are susceptible to van der Waals forces due to their large specific surface area and surface energy in the liquid phase. Although the attraction between individual nanocellulose fibers is relatively weak, this effect can accumulate at high concentrations, leading to fiber aggregation. In addition, in a liquid environment, nanocellulose fibers with high surface energy tend to reduce their total surface energy, which is usually achieved through fiber aggregation. Thirdly, the surface of nanocellulose usually carries an electric charge, and the interaction of these charges further promotes the aggregation of nanofibers, forming them into a specific shape.

[0090] Figure 3 is a SEM image of CNF-A@ZIF-8 / PDA prepared in Example 1. Figure 3 It can be seen that the layer thickness of CNF-A increased significantly, and a large number of ZIF-8 nanoparticles were distributed on the surface, which indicates that the in situ growth of ZIF-8 on the surface of CNF-A was successful without destroying the original structure of the layered aggregates.

[0091] Figure 4 is a SEM image of the internal structure of the CZPP rigid foam prepared in Example 1. SEM was used to characterize the microstructure of the NZPP foam. Figure 4 The multi-scale pore size (tens of microns) and multi-level hierarchical channel structure are shown in the figure. This is due to the directional structure generated by the upward volatilization of liquid nitrogen, which not only ensures the uniformity of the hollow channels. When heat energy is transferred to the NZPP foam, the hierarchical structure of the arranged skeleton effectively redirects the absorbed heat to the planar direction, reducing the heat transfer in the vertical direction.

[0092] Figure 5 is a mapping diagram of the internal structural elements of the CZPP rigid foam prepared in Example 1. Figure 5 It can be seen that C, N, O, and Zn elements are evenly distributed in its skeleton structure, indicating that ZIF-8 nanoparticles are evenly distributed in its multi-level layered framework. This helps dissipate the energy of mechanical stress, and its multi-level layered structure has a load-bearing effect similar to that of a "reinforced concrete" structure, significantly improving its mechanical strength.

[0093] Figure 6 is a macroscopic photograph of the CZPP rigid foam prepared in Example 1. Figure 6 It can be seen that NZPP foam has a low density (57.7 mg / cm 3), the mechanical strength is stable, and it can easily withstand a weight of 1.0kg. This shows that the load-bearing structure of the "reinforced concrete" structure produced by specific directional freezing has greatly enhanced the mechanical strength of CZPP rigid foam, and its load-bearing structure in the vertical direction has played a good compressive resistance, allowing CZPP rigid foam to easily withstand hundreds of times its own weight.

[0094] Figure 7 and Figure 8 They are the infrared thermal imaging image and temperature change image of the CZPP rigid foam prepared in Example 2 on the hot plate. Figure 7 and Figure 8 It can be seen that the presence of many tiny hollow channels in the CZPP foam structure inhibits gas convection, and the flow of gas inside the foam is hindered, thereby reducing the transfer of heat convection. In addition, the gas (such as air) in the CZPP rigid foam has a lower thermal conductivity. Compared with solid materials, the gas has poor thermal conductivity, which can effectively reduce the conduction of heat through the material. Therefore, CZPP foam exhibits excellent thermal insulation performance on the hot plate.

[0095] Fig. 9 and Fig.10 The infrared thermal imaging image and temperature change image of the CZPP rigid foam prepared in Example 3 on a cold plate. Fig. 9 and Fig.10 It can be seen that, similar to the principle of thermal insulation, CZPP rigid foam can prevent heat from the top from being transferred to the bottom. Its extremely low thermal conductivity effectively prevents phonon scattering inside the material, inhibits the transfer of temperature, and makes it exhibit good thermal insulation performance.

[0096] Fig.11 is the thermal conductivity diagram of CZPP rigid foam and other thermal insulation materials prepared in Example 4. Fig.11 It can be seen that NZPP foam has an extremely low thermal conductivity (0.048W / mK), which is comparable to commercial thermal insulation building materials (0.050W / mK). This allows CZPP rigid foam to effectively reduce heat conduction and maintain temperature stability, and is often used in building insulation, refrigeration equipment and thermal protection systems.

[0097] Fig.12It is the surface friction coefficient curve diagram of the CZPP hard foam prepared by embodiment 1, proves that ZIF-8 nanocrystal can improve the anti-friction and anti-wear performance of composite material, because they can not only play a good rolling effect in the friction process, its flexible crystal deformation can promote the rapid transmission of friction energy, and quickly stabilizes the friction coefficient. In addition, due to the hard structure of CZPP foam, a basis is provided for its wear resistance. In the test process, the friction coefficient curve under low load presents a gradually rising trend, indicating that the friction pair surface contact is not sufficient, and the fluctuation of the friction coefficient is large. The increase of load can promote the contact between the friction pair to be more sufficient, and the lubricating material can be released and gradually stabilize the friction coefficient along with the increase of the wear time.

[0098] Fig.13 is a surface wear morphology of the CZPP rigid foam prepared in Example 1. Fig.13 It can be found that obvious scratches appear on the surface of CZPP rigid foam, but the surface structure is not destroyed, indicating that it has excellent wear resistance.

[0099] Although the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as limiting the present invention.

Claims

1. A method for preparing a wear-resistant and heat-insulating rigid foam material, characterized in that: The following steps are involved: Step 1, treating cellulose with a deep eutectic solvent consisting of choline chloride and oxalic acid dihydrate to convert it into nanofibril CNF, and filtering and washing the CNF to remove excess solvent; Wherein, by weight, the amount of choline chloride is 40-45 parts, the amount of oxalic acid dihydrate is 30-35 parts, and the amount of cellulose is 8-10 parts; Step 2, dispersing the CNF prepared in step 1 in distilled water and freezing it, and then freeze-drying it to obtain nanocellulose aggregates CNF-A with a layered structure; Wherein, by weight, the amount of CNF is 5 to 10 parts, and the amount of distilled water is 200 to 300 parts; Step 3, dispersing the CNF-A prepared in step 2 in methanol and adding zinc nitrate hexahydrate and dimethylimidazole, stirring continuously for 18 to 24 hours, filtering and washing to obtain CNF-A@ZIF-8; Wherein, in parts by weight, the amount of CNF-A is 5 to 10 parts, the amount of methanol is 500 to 800 parts, the amount of zinc nitrate hexahydrate is 6 to 10 parts, and the amount of dimethylimidazole is 16 to 21 parts; Step 4, dispersing the CNF-A@ZIF-8 and dopamine hydrochloride prepared in step 3 in a Tris buffer and stirring the dispersion at room temperature for 20 to 24 hours to obtain CNF-A@ZIF-8 / PDA, and obtaining a CNF-A@ZIF-8 / PDA solid by freeze drying; Wherein, by weight, the amount of CNF-A@ZIF-8 is 5 to 8 parts, the amount of dopamine hydrochloride is 17 to 24 parts, and the amount of Tris buffer is 800 to 1200 parts; Step 5, dispersing the CNF-A@ZIF-8 / PDA prepared in step 4 in distilled water to obtain a dispersion slurry, and adding 10 wt % polyvinyl alcohol aqueous solution and epichlorohydrin to the slurry for stirring and mixing to obtain a CNF-A@ZIF-8 / PDA / PVA precursor, namely a CZPP precursor; Among them, in parts by weight, the amount of CNF-A@ZIF-8 / PDA is 5 to 10 parts, the amount of distilled water is 100 to 150 parts, the amount of polyvinyl alcohol aqueous solution is 150 to 200 parts, and the amount of epichlorohydrin is 15 to 20 parts; Step six, placing the CZPP precursor prepared in step five in a mold for freezing treatment, and then freeze-drying to obtain CZPP rigid foam.

2. The method for preparing the wear-resistant and heat-insulating rigid foam material according to claim 1, characterized in that: The method for treating cellulose with a deep eutectic solvent in step 1 is to mix the raw materials and then heat and stir them at 100 to 120° C. for 3 to 6 hours.

3. The method for preparing the wear-resistant and heat-insulating rigid foam material according to claim 1, characterized in that: The washing method described in step 1 is washing with distilled water 3 to 5 times.

4. The method for preparing the wear-resistant and heat-insulating rigid foam material according to claim 1, characterized in that: The freezing treatment described in step 2 and step 6 is freezing at -18 to -20°C for 12 to 16 hours; The freeze-drying process described in step 2, step 4 and step 6 is freeze-drying at -56 to -64°C for 48 to 50 hours.

5. The method for preparing the wear-resistant and heat-insulating rigid foam material according to claim 1, characterized in that: The washing method described in step 3 is to wash once with methanol and then wash 3 to 5 times with ethanol.

6. The method for preparing the wear-resistant and heat-insulating rigid foam material according to claim 1, characterized in that: The preparation method of the Tris buffer described in step 4 includes: adding 3.0285g Tris to 500mL distilled water, and then adding 0.6125mL concentrated hydrochloric acid and shaking well; the pH of the Tris buffer is 8.

5.

7. The method for preparing the wear-resistant and heat-insulating rigid foam material according to claim 1, characterized in that: The stirring in step 5 is carried out by using a magnetic stirrer for 30 to 40 minutes.

8. A wear-resistant and heat-insulating rigid foam material prepared by the method according to any one of claims 1 to 7.

Citation Information

Cited By

  • Halogen-free flame-retardant high-heat-insulation high-strength cable belting composite material and preparation method thereof

    CN120005500A

  • Modified bio-based polymer and preparation method thereof

    CN120289755A